Understanding Disparities in Punishment: Regulator Preferences and Expertise - Kang, Karam; Silveira, Bernardo S. (Journal of Political Economy, 2021)
This paper quantifies the benefits of discretion in the enforcement of environmental regulations. We identify and estimate a structural model of regulator-discharger interactions, exploiting an increase in the enforcement stringency of water pollution regulations in California. Our estimates indicate that most of the heterogeneity in punishments for observably similar violations is due to heterogeneity in discharger compliance costs rather than heterogeneity in regulator preferences. We find that removing the discretion of regulators to tailor punishments to discharger attributes would raise enforcement costs and decrease compliance by dischargers with high social harms of violations.